1953
DOI: 10.1002/cber.19530860111
|View full text |Cite
|
Sign up to set email alerts
|

Über pflanzliche Herzgifte, XXI. Mitteil.: Die herzwirksamen Verbindungen von Bowiea volubilis Harvey und Bowiea kilimandscharica Mildbread

Abstract: Aus Bowiea volubilis Harvey (große, grüne Sorte) wurde ein neues Glykosid, das Bovosid D, C31H44O10, isoliert, das Thevetose als Zuckerkomponente enthält. Ferner wurden 2 nicht bekannte Aglykone, das Bovogenin E mit der möglichen Formel C24H34O9 (+2CH3CO?) und das Kilimandscharogenin A, C24H34O5, erhalten. Das letztgenannte Aglykon konnte auch aus Bowiea kilimandscharica Mildbread gewonnen werden, neben einer weiteren vermutlich zuckerfreien Verbindung, die als Kilimandscharogenin B (C24H34O9 + 2CH3CO?) bezeic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1955
1955
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Concentrated sulfuric acid (322) and fuming sulfuric acid (12) give characteristic colors or fluorescence with many steroids (462,13,6,281,425,316)8 but the filter paper soon disintegrates. The Liebermann-Burchard reagent (sulfuric acid-acetic anhydride) (298,235,215,316,119,429) is less destructive but gives a fluorescence similar to that of the more convenient 15 per cent phosphoric acid reagent proposed by Neher and Wettstein (282).…”
Section: A Detection Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concentrated sulfuric acid (322) and fuming sulfuric acid (12) give characteristic colors or fluorescence with many steroids (462,13,6,281,425,316)8 but the filter paper soon disintegrates. The Liebermann-Burchard reagent (sulfuric acid-acetic anhydride) (298,235,215,316,119,429) is less destructive but gives a fluorescence similar to that of the more convenient 15 per cent phosphoric acid reagent proposed by Neher and Wettstein (282).…”
Section: A Detection Methodsmentioning
confidence: 99%
“…Digitalis glycosides have been analyzed qualitatively (264,265,234,293,297,294,295,208,209,150,61,62,440,350,404) and quantitatively (210,385,386,422,106,25,23,24). Other genera examined for cardiac glycosides by partition chromatography were Scilla (403, 119), Bowiea (215, 425), Urechites (162), Nerium (330), Acokanthera (279), Cheiranthus (275), Periploca (360), and Convallaria (424).…”
Section: E Plant Steroidsmentioning
confidence: 99%
“…299 Katz and Tschesche et al have between them reported the presence of several bufadienolides (bovisides A 560, B, C, D, bovogenin E, bowieasubstanz G, glucobovoside A 561, nabogenin (scilliglaucosidin) 532, bovoruboside 562 and bovogenin A 563) between the years of 1950 and 1959. [300][301][302][303][304][305][306][307][308][309][310][311][312][313][314] Structures have been reported for nabogenin 532, bovoruboside 562, bovoside A 560, glucobovoside A 561 and bovogenin A 563, although the structure reported for bovoruboside is not certain. The cardioactive glycosides from B. volubilis attracted much attention in the early years of their discovery.…”
Section: The Urgineoideaementioning
confidence: 99%
“…The same anthocyanins were produced with some small changes in the percentage composition of the different compounds. 132 The red owers of H. orientalis likewise produced a range of acylated anthocyanins (303)(304)(305)(306)(307)(308)(309)(310)(311)(312)(313)(314)(315)(316) and, as with the blue owers, the red owers produced in vitro produced the same anthocyanins with some differences in composition. [133][134][135] A later investigation of the blue owers of H. orientalis revealed a further seven anthocyanins (317)(318)(319)(320)(321)(322)(323) in addition to those isolated previously.…”
mentioning
confidence: 94%
“…2 Active glycosides were isolated by Jaretzky,3 and homogeneous bufadienolides were independently obtained by Katz,4 and Tschesche and Sellhorn. 5 In previous publications from these laboratories the results on bovoside A and D, and bovogenin E were discussed.6,7 Tschesche and his associates8 recently changed the names of bovoside D and bovogenin E to bovochrysoide and bovoeolotoxin, respectively.…”
mentioning
confidence: 99%